ALTERATION OF PHARMACOKINETIC PARAMETERS OF PROTON PUMP INHIBITORS USING TRANSDERMAL DRUG DELIVERY SYSTEM - SHIVALINGAM, M. R.; BALASUBRAMANIAN, ARUL; RAMALINGAM, KOTHAI (International Journal of Applied Pharmaceutics, 2021)
Objective: The present study was aimed to find out the effect of transdermal patches of proton pump inhibitors pantoprazole and esomeprazole on the alteration of pharmacokinetic parameters of these drugs. Methods: The transdermal patches were formulated by the solvent evaporation technique using polymers HPMC E5 with PVP K 30 and HPMC E5 with Eudragit L100 in different ratios. The best formulation from each of the drug pantoprazole and esomeprazole was selected and administered to rabbits and the plasma drug concentration was compared with the marketed formulation. The pharmacokinetic parameters such as maximum plasma concentration (Cmax), time to reach Cmax (tmax), area under the curve (AUC), area under first moment curve (AUMC), elimination rate constant (λz), biological half-life (t1/2), and mean residence time (MRT) were determined. Results: The plasma drug concentration vs time curve shows the extended-release of the drugs pantoprazole and esomeprazole when compared with the marketed formulation. The results show that there is no change in the peak plasma concentration, but a significant difference was observed in all the pharmacokinetic parameters. The AUC showed 6 fold increase for pantoprazole from 8.91 to 55.20 μg*h/ml and 3.5 fold increase for the drug esomeprazole from 7.86 to 28.53 μg*h/ml, and the mean residence time also showed 2 fold increase for the transdermal patches when compared with the marketed formulations. Conclusion: The increase in tmax, AUC, and MRT values of the formulated transdermal patches with the values of the marketed formulation of both the drugs, revealed that the transdermal patches can be used to deliver the drug for an extended period and also can alter the pharmacokinetics of pantoprazole and esomeprazole.